Zhu shi nongjia bao, fei shi tianzhong jin - Yan Wenzheng,
'A pig is the treasure in a farmer's house, his fat is the gold in the fields, if you feed a pig you can store the fat and benefit the country and the people.' Printno. T8087.844.